Association between dietary intake of vitamin A, C, and E as antioxidants and cognitive function in the elderly at a nursing home (Medical Journal of Indonesia, 2007)
As oxidative stress is considered one of the major mechanisms underlying degenerative changes, antioxidants from dietary sources, such as vitamin A, C, and E, may have protective effects against oxidative stress and thus be able to prevent or delay cognitive impairment in the elderly. This cross sectional study was designed to determine the association between dietary intake of vitamin A, C, and E and the presence of cognitive impairment in the elderly, along with other factors. Subjects included 36 residents from a nursing home in Jakarta, Indonesia. The data obtained including daily nutrition intake values one week prior to sampling converted from semi- quantitative food frequency questionnaire (SFFQ) results, Mini Mental State Examination (MMSE) scores, and anthropometrical measurement results. This study showed that while sex, age, education, nutritional status, and macronutrients intake were not significantly associated with presence of cognitive impairment, significant positive correlation existed between education and MMSE score (p=0.036, r=0.351). Higher vitamin A and vitamin C intake were shown to be significantly associated with lower incidence of cognitive impairment (p=0.022 and p=0.045, respectively). Moreover, vitamin C was shown to have significant positive correlation with MMSE score (p=0.031, r=0.359). However, the association between vitamin E and the presence of impairment was not significant (p=0.129). Higher intake of vitamin A and C may delay or prevent cognitive impairment in the elderly. Higher intake of vitamin C may contribute to better cognitive functioning. The findings may be explained by the two antioxidant vitamins' protective effects against neurode generative processes cause by oxidative stress. (Med J Indones 2007; 16:261-6)